The Value of Effective Lung Ventilation Area Ratio Based on CT Image Analysis Is a New Index to Predict the Shorter Outcome of Anti-melanoma Differentiation-Associated Protein 5 Positive Dermatomyositis Associated Interstitial Lung Disease: A Single-Center Retrospective Study - Wang, Changjian; Du, Jinfeng; Mei, Xilong; Guo, Lingchao; Li, Fangzhao; Luo, Hong; Li, Fen (Frontiers in Medicine, 2021)
Background: Anti-melanoma differentiation-associated protein 5 (MDA5) positive dermatomyositis (MDA5+DM) patients have poor outcomes due to rapidly progressive interstitial lung disease (ILD). The accurate assessment of lung involvement is an urgent focus of research. Methods: A computer-aided lung interstitial image analysis technology has been developed, and a quantitative indicator named effective lung ventilation area ratio (ELVAR) that calculates the proportion of the area outside the lung interstitium in lung tissue has been established. Fifty-five newly diagnosed MDA5+DM patients and 46 healthy individuals, matched for age and gender, were enrolled in this study. MDA5+DM patients were classified into early death group or early survival group according to their survival state within 3 months after diagnosis. Clinical characteristics, laboratory and immunological test results, lung involvement (including ELVAR value) and treatment were compared between early death group and early survival group to determine an index that can predict prognoses of patients with MDA5+DM. Results: There were significant differences between early death MDA5+DM patients and early survival MDA5+DM patients about 12 indices including age of onset, CRP, ferritin, albumin, and pulmonary involvement including severity of type I respiratory failure at diagnosis, P/F ratio, oxygen supplementation, values of ELVAR, FVC and DLCO. The results of ROC analysis and correlation analysis showed the value of ELVAR had good diagnostic value and widely correlation with many clinical characteristics. Univariate analysis and Multivariate analysis showed 4 factors including age of onset, ferritin, value of ELVAR and oxygen supplementation >4L/min significantly value for poor prognosis in MDA5+DM patients. A cutoff value of 0.835 about ELVAR had good predictive power for mortality within 3 months in 54.2% of MDA5+DM patients. Conclusions: The value of ELVAR derived from computed tomography image analysis is a new index that can predict poor outcomes in patients with MDA5+DM with rapidly progressive interstitial lung disease.